Trabajo colegiado y profesionalidad docente en la institución educativa N° 64479 Pastor Valencia Cushillo Cocha, Distrito de Ramón Castilla 2023 - Sosa Campos, Alain Rosemberg (2025)
The objective of this study was to investigate the relationship between collegial work and professional teaching performance at the between collegial work and teacher professionalism at the public secondary school public secondary school N° 64479 Pastor Valencia Peña de Cushillo Cocha. This research is a quantitative, descriptive correlational, with a non-experimental design. The population consisted of 35 teachers. The sample used was 100% of the total population. The survey technique was applied and questionnaires were used as instruments. The most relevant conclusions were the following: There is a high, direct and positive significant relationship between collegial work and teaching professionalism. By applying Pearson's correlation coefficient (Rho= 0.741) and an approximate significance of 0.002 (p < 0.01), it can be interpreted that, as the level of collegial work increases, the increase in the level of teaching professionalism will also be favored. This allows us to accept the hypothesis of the study.